Atividade antifúngica do óleo essencial de Melissa officinalis L. (erva-cidreira) e de sua associação com antifúngicos licenciados sobre Candida albicans. - Leitão, Maíra Catherine de Negreiros (2016)
Oral candidiasis is a fungal infection caused by yeasts of the genus Candida, with C. albicans being the main pathogen. The emergence of resistant species against the available therapeutic arsenal as well as its adverse effects has driven new research on natural products. In view of this problem, the present study sought to investigate the antifungal activity of essential oil (OE) obtained from the leaves of Melissa officinalis L (lemon balm), isolated and associated with antifungal agents licensed on C. albicans strains. Two strains of the American Type Culture Collection (ATCC) and eight from the oral cavity (LM) were selected. The microdilution and sowing of subcultures were used to determine, respectively, the Minimum Inhibitory Concentration (MIC) and Minimum Fungicidal Concentration (CFM). The antifungigram was performed using the disc diffusion technique with the antifungal agents nystatin, amphotericin B, miconazole and fluconazole, evaluating them in isolation and associated with OE. MIC and MFC ranged from 64 to 128 μg/mL and 256 to 512 μg/mL, respectively. The presence of resistance of the strains to the antifungal agents nistatin (LM-38 and LM-65), amphotericin B (ATCC-76485, LM-3A, LM-38, LM-62 and LM -65) and fluconazole (LM-1A, LM- 1B, LM-38, LM-62 and LM-65). In the association tests, the results showed the influence of the essential oil on the antifungal activity, with synergism (S), indifference (I) and antagonism (A) being observed. The percentages found for each antifungal in the order (S, I and A) were: nystatin (30%, 30% , 40%), amphotericin B (30%, 50%, 20%), fluconazole (20% ,40% , 40%) and miconazole (100%, 0,0). In view of the above, it is concluded that the OO of M. Officinalis may become a promising product in the fight against oral candidiasis, since it has a strong antifungal activity against Candida albicans and that the use of this product associated with the licensed antifungal can, in some situations, potentiate its effectiveness of use in treatment.